Identification of a glycan cluster in gp120 essential for irreversible HIV-1 lytic inactivation by a lectin-based recombinantly engineered protein conjugate. Issue 21 (13th November 2020) - Parajuli, Bibek; Acharya, Kriti; Nangarlia, Aakansha; Zhang, Shiyu; Parajuli, Bijay; Dick, Alexej; Ngo, Brendon; Abrams, Cameron F.; Chaiken, Irwin
Abstract : We previously discovered a class of recombinant lectin conjugates, denoted lectin DLIs ('dual-acting lytic inhibitors') that bind to the HIV-1 envelope (Env) protein trimer and cause both lytic inactivation of HIV-1 virions and cytotoxicity of Env-expressing cells. To facilitate mechanistic investigation of DLI function, we derived the simplified prototype microvirin (MVN)-DLI, containing an MVN domain that binds high-mannose glycans in Env, connected to a DKWASLWNW sequence (denoted 'Trp3') derived from the membrane-associated region of gp41. The relatively much stronger affinity of the lectin component than Trp3 argues that the lectin functions to capture Env to enable Trp3 engagement and consequent Env membrane disruption and virolysis. The relatively simplified engagement pattern of MVN with Env opened up the opportunity, pursued here, to use recombinant glycan knockout gp120 variants to identify the precise Env binding site for MVN that drives DLI engagement and lysis. Using mutagenesis combined with a series of biophysical and virological experiments, we identified a restricted set of residues, N262, N332 and N448, all localized in a cluster on the outer domain of gp120, as the essential epitope for MVN binding. By generating these mutations in the corresponding HIV-1 virus, we established that the engagement of this glycan cluster with the lectin domain of MVN*-DLI is the trigger for DLI-derived virus and cell inactivation. Beyond defining the initial encounter step for lytic inactivation, this study provides a guide to further elucidate DLI mechanism, including the stoichiometry of Env trimer required for function, and downstream DLI optimization.